Interprofissionality: from theory to practice provided by PET-HEALTH (Research, Society and Development, 2022)
Objective: To share experiences of the PET-Saúde team with interprofessional education and collaborative practices in Primary Health Care (PHC). Methodology: This is a descriptive study, of the experience report type, which had as its field of experience a group of body practices from an Expanded Family Health Center (NASF) linked to the Municipal Health Unit (UMS), located in the city of Belém, state of Pará, during the period of nine months, from April 2019 to January 2020. Results and discussion: The experience allowed the merging of knowledge and the exchange of experience among the team; thus leading to greater accuracy in the care followed by the professionals, and diversification of health education for the students present. Conclusion: The academic approach with the scenarios of the Unified Health System (SUS) favored a greater engagement in the understanding of public health policies and thus stimulating clinical reasoning in search of the effectiveness of actions, therefore, it is suggested that the Program Education through Work (PET) Health continues to enable these exchanges of fundamental knowledge in academic training, involving the academic-professional-user triad, causing in great improvments in the quality of care provided in the territory.